Grievance Redress Mechanisms in the Health Sector in Mozambique - POTENCIAR (POTENCIAR, 2023)
Context: This research stemmed from learning and changes that occurred in the intervention strategy and budget of the POTENCIAR programme. In consultations and meetings between the Programme Management Unit (UGP) and various actors operating in this area, POTENCIAR’s partners identified — in a participatory and inclusive manner — the issue of grievance redress mechanisms as a problem that they can intervene on within the context of Pro-Accountability Initiatives (PAIs). Taking this perspective , POTENCIAR conceived the present research on mechanisms for complaining about and denouncing poor standards in maternity services. Objectives: The objective of this study was to understand the complaints and grievances management system available to users in the health sector. The insights gained from this study will subsequently feed back into revision s to POTENCIAR’s theory of change and theory of action. The research included mapping the flow of the complaint channel ling process; identifying the motives, capacities, and opportunities for the health authorities to implement the system of mechanisms for redressing complaints; an analysis of how the perspectives of users are perceived, considered, and rejected by health authorities; and, finally, an analysis of the extent to which existing grievance mechanisms are used, including the opportunities, capacities, and motivations for using them.
Keywords: *non-public; G - Mozambique / Moçambique; L - english / inglês; governance / governação; health / saúde; mecanismos de reclamação / grievance redress mechanisms

Análise dos Efeitos Socioeconómicos das Taxas de Usuário no Sector Público de Saúde - OCS (Observatório do Cidadão para Saúde, 2022)

A aceleração da financeirização: respostas das instituições financeiras internacionais à pandemia da COVID-19 em Moçambique - Barroso, Edgar; Castel-Branco, Ruth; Monjane, Boaventura (Desafios para Moçambique 2022, 2022)
O estudo conclui que as IFI aproveitaram este momento de crise para acelerar a financeirização do desenvolvimento; porém, também ilustra a resistência tanto do Estado como da sociedade civil. Se essas formas de resistência podem ou não contribuir para a construção de um Estado desenvolvido robusto depende do poder dos movimentos sociais globalizados para reaver o controlo e sacá-lo das garras do capitalismo financeiro. A primeira secção situa as respostas políticas do FMI e do Banco Mundial à pandemia da covid-19, numa análise histórica. Em 1987, Moçambique embarcou no seu primeiro programa de ajustamento estrutural, liberalizando a economia e eliminando impostos e tarifas; privatizando serviços públicos, empresas e activos; e desregulando as protecções sobre o consumidor e o trabalho. Essas medidas resultaram em cortes maciços na despesa, austeridade e dívida pública. A dívida de Moçambique foi subsequentemente cancelada, mas o FMI continuou a controlar a sua economia através do Instrumento de Apoio às Políticas. Actualmente, o Banco Mundial financia projectos que rondam os 3,7 mil milhões de dólares, ou o equivalente ao orçamento anual de Moçambique. O sector agrícola representa 14% do investimento e a protecção social, 9%. A segunda secção demonstra como o Banco Mundial utilizou a pandemia da covid-19 para impor a sua agenda de protecção social de duas formas importantes. Em primeiro lugar, substituindo a ideia de direitos universais por concessões altamente selectivas, de curto prazo e residuais ao arrepio das causas na raiz da pobreza e da desigualdade. Segundo argumentavam, as necessidades de longo prazo poderiam ser abordadas mais eficazmente pela diversificação dos meios de subsistência e a incorporação dos agregados familiares em situação de pobreza nos mercados financeiros através do crédito e da dívida. Em segundo lugar, tentando financiar as transferências monetárias pela externalização de sistemas de pagamento a prestadores de serviços financeiros. Embora esses condicionalismos se tenham revelado impossíveis de implementar e o Governo tenha acabado por ter de internalizar o programa, todo esse fiasco teve um custo material e humano considerável para os Moçambicanos. A terceira secção explora a abordagem do Banco Mundial à agricultura. Apesar de reconhecer que Moçambique tem uma lei da terra progressista, há muito que o Banco Mundial faz pressão pela colateralização da terra, a incorporação dos agricultores em cadeias produtos de base globais e a expansão da agricultura de grande escala, orientada para o mercado. Contudo, como ilustra a destruição da indústria do caju, os resultados são muitas vezes contraditórios. Recentemente, o Banco Mundial reorientou o seu apoio para a agricultura de pequena escala, adoptando o projecto Sustenta. O apoio aos pequenos proprietários e agricultores camponeses tem-se articulado com a privatização e a colateralização da terra. Com efeito, o lançamento do Sustenta coincide com a revisão da própria lei da terra que tinham elogiado como sendo progressista. Como conclui o capítulo, a pandemia criou uma oportunidade para o Banco Mundial acelerar a financeirização pela instrumentalização de empréstimos e subvenções. Isto levou à tentativa de expropriação do Estado moçambicano e da sua população através da externalização das funções do Estado e da privatização dos activos do Estado. Não obstante, os momentos de crise criam janelas de oportunidade para reorientar a política e a acção no sentido da construção de um estado desenvolvido. O capítulo insta a uma maior articulação entre os movimentos sociais - sejam eles sedeados no lar, no campo, na esquina, ou na fábrica - para unir forças contra a onda de expropriações, exploração e neoliberalismo tardio. Além disso, apela a que se reanime o movimento da justiça global para que seja possível responsabilizar as instituições financeiras internacionais
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; L - portuguese / português; health - COVID-19 / saúde – COVID-19

Avaliação do Impacto da Subcomponente Subsídio para Crianças dos 0 aos 2. Componente de Subsídio para Criança do Programa Subsídio Social Básico na Província de Nampula em Moçambique Relatório da Pesquisa Final (24 meses) - Bonilla, Juan; Castro-Zarzur, Rosa; Seidenfeld, David; Peterman, Amber; Bruckauf, Zlata (American Institutes for Research e UNICEF, 2022)
Este relatório fornece os resultados finais da avaliação do Subsídio para Criança 0-2 de Moçambique. O Subsídio Criança 0-2 é um subcomponente do Programa de Subsídio Social Básico (PSSB), um programa nacional liderado pelo Ministério de Gênero, Criança e Ação Social (MGCAS). A avaliação coincide com a fase de arranque da intervenção, que aconteceu até 2021 em quatro distritos seleccionados da província de Nampula. A intervenção segue uma metodologia de 'dinheiro e cuidado' e inclui três componentes: (1) transferências de dinheiro, (2) um pacote de comunicação para a mudança social e de comportamentos (CMSC) com ênfase em nutrição (3) uma gestão de casos em temas de proteção social para os mais vulneráveis. A intervenção visa reduzir a pobreza e a vulnerabilidade social, fornecendo transferências em dinheiro para as cuidadoras principais de crianças pequenas com o objetivo geral de reduzir a pobreza, melhorar o bem-estar infantil e promover o acesso a serviços sociais básicos. Além disso, o componente de cuidados da intervenção pretende abordar a proteção complexa e inter-relacionada, bem como os riscos sociais, econômicos e de saúde, que as famílias-alvo enfrentam. A intervenção começou a ser implementada em setembro de 2018, e esta avaliação fornece evidências críticas sobre sua eficácia para informar a melhor forma de expansão da intervenção.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Ilha de Moçambique; GD - Lalaua; GD - Mogincual; GD - Nacala-a-Velha; GP - Nampula; L - portuguese / português; health - maternal and child / saúde - materno-infantil; social protection / proteção social

Mulheres lutando contra o HIV/SIDA: cuidadoras de Moçambique - Casimiro, Isabel Maria; Fauré, Yves-A; Tembe, Carlota Mondlane; Mutisse, Luisa Chicamisse (Desafios para Moçambique 2022, 2022)
Moçambique é um país caracterizado por índices elevados de pobreza onde a prevalência do Vírus da Imunodeficiência Humana (HIV)/Síndrome da Imunodeficiência Adquirida (SIDA) é muito alta e a taxa de incidência ainda preocupante, e cujos meios de combate à doença são limitados e dependem, em parte, da ajuda externa. A súbita emergência e rápida expansão da covid-19, a partir do início de 2020, teve um impacto negativo nas condições de tratamento das PVHIV, que, de certa forma, sofreram uma dupla aflição. Os serviços de saúde essenciais foram afectados - prevenção, diagnóstico, tratamento, cuidados paliativos e reabilitativos, etc. - com efeitos graves nos doentes mais vulneráveis (crianças, idosos, pessoas que vivem com doenças crónicas). Com este estudo, pretendemos apresentar os resultados obtidos através da divulgação das iniciativas das mulheres junto às autoridades públicas, instituições nacionais e internacionais, agências de cooperação bilaterais, associações e ONGs moçambicanas e estrangeiras dedicadas de uma ou de outra forma à luta contra o HIV/SIDA. Finalmente, almejamos examinar as condições em que estas iniciativas poderiam ser integradas ou pelo menos aproximadas das Unidades Sanitárias que trabalham na área do HIV/SIDA.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; gender / género; health / saúde; society / sociedade

Influência das repostas interinstitucionais coordenadas a emergências e desastres de saúde pública na resposta nacional à COVID-19 em Moçambique: Estudo de caso. - Inguane, Celso; Zimba, Victor (Desafios para Moçambique 2022, 2022)
Moçambique articulou oportunamente uma resposta nacional coordenada à covid-19, com um comando claro dos níveis mais altos do Governo central, inicialmente conceptualizada pelo sector da saúde. A resposta seguiu um modelo aparentemente híbrido, baseado numa resposta humanitária rápida usada para enfrentar calamidades naturais e numa abordagem de saúde global usada para responder a eventos de saúde pública. Estas abordagens foram institucionalizadas no País ao longo de duas décadas, caracterizadas pela liderança normativa do Governo moçambicano e apoio logístico, técnico e financeiro dos parceiros de cooperação internacional, com participação limitada da sociedade civil e do empresariado local em processos de tomada de decisão sobre a concepção e implementação da resposta. Este padrão de participação ficou evidente no primeiro ano da resposta à covid-19, em Moçambique. Contudo, foi também notado como padrão da resposta global a surtos de doenças infecciosas, epidemias e pandemias entre 2002 e 2015, nos seguintes termos: «muito frequentemente, o envolvimento da comunidade tem sido uma consideração a posteriori — pouco investigado, deixado para depois até que seja demasiado tarde e implementado atabalhoadamente” (Sands, Mundaca-Shah, & Dzau, 2016). O primeiro ano da resposta à covid-19, em Moçambique, revelou igualmente a presença generalizada de múltiplos mecanismos de coordenação, profundamente permeados por competições institucionais, incluindo a coexistência de múltiplos sistemas de informação em saúde, de repositórios e protocolos que não alimentavam a rotina do sistema de informação em saúde de modo que informasse uma resposta eficaz e coordenada à covid-19. Atender a tais multiplicidades requer energia e recursos que se desviavam da gestão eficaz da resposta nacional à covid-19. A dispersa legislação nacional sobre saúde pública, que não tomou em conta as necessidades de quarentena e outras restrições ao movimento de pessoas exigidas pela resposta à covid-19, agravou estas multiplicidades. O vácuo que essa escassez criou foi preenchido por uma profusão legislativa, produzida no âmbito de um Estado de Emergência, eventualmente substituído por um Estado de Calamidade Pública. Tal contribuiu para restrições ao espaço cívico (Pereira, Forquilha, & Shankland, 2021), justificadas por lógicas de governação da saúde pública. Assim, o modelo utilizado para a coordenação do primeiro ano da resposta nacional à covid-19, em Moçambique, salienta a importância de uma complexa combinação de influências sociopolíticas e de saúde pública que moldam as respostas nacionais a emergências e desastres de saúde pública no País. Tais influências incluem a exposição a pandemias nos últimos anos (Tsuei, 2020), exposição a desastres naturais a longo-prazo (Moore, Eng, & Daniel, 2003) Mozambique suffered its worst flooding in almost 50 years: 699 people died and hundreds of thousands were displaced. Over 49 countries and 30 international non-governmental organisations provided humanitarian assistance. Coordination of disaster assistance is critical for effective humanitarian aid operations, but limited attention has been directed toward evaluating the system-wide structure of inter-organisational coordination during humanitarian operations. Network analysis methods were used to examine the structure of interorganisational relations among 65 non-governmental organisations (NGOs e a interesses institucionais locais e globais (Fassin, 2012), incluindo a secundarização do envolvimento comunitário, notado com um padrão global (Sands, Mundaca-Shah, & Dzau, 2016) também documentados em países de língua oficial portuguesa (LEIASS, 2020).
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; health - COVID-19 / saúde – COVID-19; politics / política

As relações Brasil-África no contexto da pandemia da COVID-19. Cooperação com Moçambique - Marcondes, Danilo (Desafios para Moçambique 2022, 2022)
A pandemia da covid-19 rapidamente se impôs como um dos principais, se não o principal, tema de política internacional, no período entre 2020 e 2022. A pandemia exacerbou desafios já encontrados pela comunidade internacional, como as restrições de mobilidade, assim como o acesso desigual a medicamentos e vacinas. Em certos contextos autoritários, as iniciativas de lockdown e distanciamento também foram mobilizadas para restringir as liberdades civis e de organização política. Certas respostas à pandemia também reforçaram o populismo com a adopção de um discurso negacionista, anti ciência e contrário a instituições multilaterais como a Organização Mundial de Saúde (OMS). O relacionamento entre o Brasil e o continente africano, no contexto da covid-19, precisa ser entendido a partir desses desafios e dos impactos que os mesmos deixaram na política internacional. No mesmo período, em Janeiro de 2022, o início do mandato brasileiro como membro nãopermanente do Conselho de Segurança das Nações Unidas (CSNU) também reforça os laços e interesses mútuos de cooperação entre o Brasil e o continente africano. Historicamente, a presença do Brasil no CSNU, principalmente no período do imediato pós-Guerra Fria, foi utilizada a favor dos países africanos parceiros, principalmente Angola e Moçambique. Em contrapartida, a maioria dos países africanos, em especial os países lusófonos, votam recorrentemente a favor das candidaturas brasileiras ao CSNU (Ministério das Relações Exteriores, 2021a). De forma a contribuir para uma melhor compreensão das dinâmicas apresentadas acima, o presente capítulo está dividido nas seguintes secções: uma análise geral sobre o acompanhamento da evolução da pandemia da covid no continente africano por parte dos diplomatas brasileiros, seguida de uma discussão sobre a cooperação brasileira no context da pandemia, e de uma secção sobre a covid-19 e as relações Brasil-Moçambique. O capítulo termina com a apresentação da conclusão. A pesquisa é beneficiada pelo acesso à documentação diplomática brasileira disponível via legislação brasileira de acesso à informação. Os documentos diplomáticos consultados incluem mensagens trocadas entre as diferentes embaixadas brasileiras, em especial a Embaixada do Brasil em Maputo-Brasemb Maputo, localizadas no continente africano e a Secretaria de Estado das Relações Exteriores (SERE), em Brasília.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; health - COVID-19 / saúde – COVID-19; south-south cooperation / cooperação sul-sul

Classes of working women in Mozambique: an integrated framework to understand working lives - Stevano, Sara (Review of International Political Economy, 2022)
Feminist political economy has illuminated the gendered dimensions of the globalisation of production. Whilst this literature provides essential insights on gendered exploitation in export-oriented industries, women’s work in localised labour markets in the Global South remains underexplored. This paper seeks to address this gap by putting into dialogue three bodies of literature – feminist political economy of globalisation, political economy of development in southern Africa and the social reproduction of the everyday. It proposes an integrated conceptual framework to analyse women’s working lives and applies it to northern Mozambique. It makes two key findings. First, the lives of those working in localised labour markets are shaped by global capitalism through extreme fragmentation of labour regimes forcing people into multiple precarious forms of work – a process that entails the appropriation of women’s productive and reproductive labour. Second, the imperatives of social reproduction shape employment trajectories and expose differentiation among working women, seen for example through gendered constraints to mobility, care obligations and contributions to ceremonies. The implications are that the analysis of women’s working lives needs to capture three key aspects: social differentiation among working women, temporal and spatial dynamics of the everyday and the centrality of the reproduction of the social.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; gender / género; labour regimes / regimes de trabalho; social protection / proteção social; social reproduction / reprodução social

Monitoria comunitária independente ao PASD-PE COVID-19. Segunda Fase - Maputo e Namaacha - Plataforma da Sociedade Civil Moçambicana para a Protecção Social (PSC-PS) (Plataforma da Sociedade Civil Moçambicana para a Protecção Social (PSC-PS), 2021)
Os principais resultados da monitoria realizada em Montepuez destacaram a necessidade de: • Fortalecimento de mecanismos comunitários de participação e reforço do diálogo social entre comunidades e governo local; • Maior apropriação dos programas de protecção social básica por parte das comunidades e a necessidade de atribuir mais voz e protagonismo dos beneficiários sobre os serviços sociais prestados a nível destes programas; • Melhor comunicação e disseminação de informação estratégica sobre os programas de protecção social junto às comunidades, incluindo mais clareza sobre critérios de elegibilidade, valor dos benefícios, periodicidade e duração; • Maior mobilização social com vista a promover comunidades mais informadas e capacitadas para reivindicar os seus direitos sociais básicos; • Reforço de mecanismos de reclamações e queixas (clareza sobre como acessá-los); • Maior apoio para facilitação do acesso dos beneficiários aos pagamentos, em particular aqueles que precisam de auxílio para utilização dos telefones a partir dos quais recebem seus benefícios; • Ampliação dos métodos de pagamento para facilitar o acesso dos beneficiários às transferências.
Keywords: G - Maputo City / Cidade de Maputo; G - Mozambique / Moçambique; L - portuguese / português; government policy / politica governamental; health - COVID-19 / saúde – COVID-19; social protection / proteção social

The role of integrated community case management projects in strengthening health systems: case study analysis in Ethiopia, Malawi and Mozambique - Story, William T; Pritchard, Susannah; Hejna, Emily; Olivas, Elijah; Sarriot, Eric (Health Policy and Planning, 2021)
Integrated community case management (iCCM) has now been implemented at scale globally. Literature to-date has focused primarily on the effectiveness of iCCM and the systems conditions required to sustain iCCM. In this study, we sought to explore opportunities taken and lost for strengthening health systems through successive iCCM programmes. We employed a systematic, embedded, multiple case study design for three countries—Ethiopia, Malawi and Mozambique—where Save the Children implemented iCCM programmes between 2009 and 2017. We used textual analysis to code 62 project documents on nine categories of functions of health systems using NVivo 11.0. The document review was supplemented by four key informant interviews. This study makes important contributions to the theoretical understanding of the role of projects in health systems strengthening by not only documenting evidence of systems strengthening in multi-year iCCM projects, but also emphasizing important deﬁciencies in systems strengthening efforts. Projects operated on a spectrum, ranging from gap-ﬁlling interventions, to support, to actual strengthening. While there were natural limits to the inﬂuence of a project on the health system, all successive projects found constructive opportunities to try to strengthen systems. Alignment with the Ministry of Health was not always static and simple, and ministries themselves have shown pluralism in their perspectives and orientations. We conclude that systems strengthening remains ‘everybody’s business’ and places demands for realism and transparency on government and the development architecture. While mid-size projects have limited decision space, there is value in better deﬁning where systems strengthening contributions can actually be made. Furthermore, systems strengthening is not solely about macro-level changes, as operational and efﬁciency gains at meso and micro levels can have value to the system. Claims of ‘systems strengthening’ are, however, bounded within the quality of evaluation and learning investments.
Keywords: G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; L - english / inglês; health / saúde

Provision and access to health services in Mozambique: An exploratory study on accountability and relations between health providers and users in Monapo district - Gonçalves, Euclides (POTENCIAR Programme, 2021)
This exploratory research set out to survey possible points of entry for POTENCIAR programme interventions and gather methodological insights for the ethnographic research component of the programme’s analytical strategy. It wil be used alongside other analytical studies undertaken by POTENCIAR (including the health sector analysis and the political economy analyses) to identify and design programme interventions. Following an inductive method, the team sought to assess the conditions and processes of health care provision and access from the perspective of health providers and residents in Monapo district in Nampula Province, northern Mozambique (POTENCIAR will implement its first PAI in Nampula province). To gain insights into accountability relations in the health sector, the team focused on the administrative and social institutions where health providers and users interact. The study asks the following question: From grounded perspectives of health providers and residents in Monapo district, what are the accountability issues in the provision and access to health services?
Keywords: *non-public; Ethnographic Studies; G - Mozambique / Moçambique; GD - Monapo; L - english / inglês; M - ethnography / etnografia; accountability / responsabilização; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - health services / serviços de saúde; health / saúde

Com quem podemos contar? Autoridade, Empoderamento e Responsabilização em Moçambique - Chaimite, Egidio; Forquilha, Salvador; Shankland, Alex (Portuguese Translation of IDS Working Paper 546, Maputo: Instituto de Estudos Sociais e Económicos, 2021)
Neste artigo, usamos 'diários de governação' para analisar as interações entre pessoas pobres e autoridades em contextos de Fragilidade, Conflitos e Violência (FCVAS) em Moçambique. Questionamos os significados de empoderamento e responsabilização, sob ponto de vista de pessoas pobres e marginalizadas, e procuramos perceber como essas pessoas vêem as instituições que as governam, incluindo as que as providenciam bens e serviços básicos, entre os quais os de saúde e segurança. As conclusões mostram que, mesmo que as percepções e, com elas, os conceitos de empoderamento e responsabilização que emergiram, não difiram significativamente dos identificados na literatura, em termos de ação e mobilização há diferenças. Constatamos que, nos nossos locais de pesquisa, as pessoas raramente se mobilizam, mesmo com a má prestação de serviços básicos e a prevalência de injustiças. Muitos consideram-se 'incapazes' de influenciar ou forçar as 'autoridades' a responderem às suas preocupações e demandas. Por 'Autoridade Pública' entendem qualquer entidade ou pessoa capaz de resolver os problemas da comunidade, enquanto Estado, geralmente reconhecido como 'Autoridade', é percebido como indistinto do Partido Frelimo e do Governo, mas também é visto como um pai, embora ausente, e aquele que se esquece e abandona os seus filhos.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; access to services / acesso a serviços; accountability / responsabilização; authority / autoridade; conflict / conflito; empowerment / empoderamento; fragility / fragilidade; governance / governação; health / saúde; institutions / instituições; justice / justiça; mobilization / mobilização; security / segurança; taxation / tributação

Who Can We Count On? Authority, Empowerment and Accountability in Mozambique - Chaimite, Egidio; Forquilha, Salvador; Shankland, Alex (IDS Working Paper 546, Brighton: Institute of Development Studies, 2021)
In this paper, we explore the use of a governance diaries methodology to investigate poor households’ interactions with authority in fragile, conflict and violence-affected settings in Mozambique. The research questioned the meanings of empowerment and accountability from the point of view of poor and marginalised people, with the aim of understanding what both mean for them, and how that changes over time, based on their experiences with governance. The study also sought to record how poor and marginalised households view the multiple institutions that govern their lives; providing basic public goods and services, including health and security; and, in return, raise revenues to fund these services. The findings show that, even if the perceptions and, with them, the concepts of empowerment and accountability that emerged do not differ significantly from those identified in the literature, in terms of action and mobilisation there are distinctions. In our research sites we found that people rarely mobilise, even faced with prevalent injustices and poor basic service provision. Many claim to be ‘unable’ to influence or force ‘authorities’ to respond to their concerns and demands.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; access to services / acesso a serviços; accountability / responsabilização; authority / autoridade; conflict / conflito; empowerment / empoderamento; fragility / fragilidade; governance / governação; health / saúde; institutions / instituições; justice / justiça; mobilization / mobilização; security / segurança; taxation / tributação

Actualidade Económica de Moçambique: Preparação para Recuperação (World Bank Group, 2021)
The global pandemic has taken a heavy toll on Mozambique’s economy. In 2020, the country experienced its first economic contraction in nearly three decades. COVID-19 (coronavirus) hit the economy as it was attempting to recover from the slowdown triggered by the hidden debt crisis and the tropical cyclones in 2019. Real gross domestic product (GDP) contracted by 1.3 percent in 2020, compared to a pre-Covid estimate of 4.3 percent, as external demand declined, domestic lockdown measures disrupted supply chains and depressed domestic demand, and liquified natural gas (LNG) investments were delayed. COVID-19 has caused a sudden income loss for enterprises and households, worsening living conditions, especially for the urban poor largely engaged in the informal sector. According to the National Institute of Statistics, as of June 2020, about 120,000 jobs were lost and 63,000 employment contracts suspended, with women being the most affected. Around 3 percent of the firms affected were forced to cease their activity. Services activities are the hardest hit. The tourism and hospitality industries have particularly suffered a steep decline in revenues. COVID-19 has jeopardized years of hard-won development gains, with about one million people estimated to have slipped into poverty in 2020 (as measured by the international poverty line of 1.90 US Dollars per day). While there is great uncertainty about the path of the pandemic, the economy is expected to gradually recover from 2021 as aggregate demand rebounds and LNG investments and extractive production gain momentum. Despite the expected recovery, the widespread deployment of COVID-19 vaccines will be at the core of a resilient recovery. This Economic Update explores the implications of COVID-19 for the economy, businesses and households. It makes recommendations for moving forward—in the short-term relief phase, as well as over the medium and longer term in order to 'build back better~^!!^.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; development partners / parceiros de cooperação; economic development / desenvolvimento económico; health - COVID-19 / saúde – COVID-19; health / saúde; private sector / setor privado

Mozambique Economic Update : Setting the Stage for Recovery (World Bank Group, 2021)
The global pandemic has taken a heavy toll on Mozambique’s economy. In 2020, the country experienced its first economic contraction in nearly three decades. COVID-19 (coronavirus) hit the economy as it was attempting to recover from the slowdown triggered by the hidden debt crisis and the tropical cyclones in 2019. Real gross domestic product (GDP) contracted by 1.3 percent in 2020, compared to a pre-Covid estimate of 4.3 percent, as external demand declined, domestic lockdown measures disrupted supply chains and depressed domestic demand, and liquified natural gas (LNG) investments were delayed. COVID-19 has caused a sudden income loss for enterprises and households, worsening living conditions, especially for the urban poor largely engaged in the informal sector. According to the National Institute of Statistics, as of June 2020, about 120,000 jobs were lost and 63,000 employment contracts suspended, with women being the most affected. Around 3 percent of the firms affected were forced to cease their activity. Services activities are the hardest hit. The tourism and hospitality industries have particularly suffered a steep decline in revenues. COVID-19 has jeopardized years of hard-won development gains, with about one million people estimated to have slipped into poverty in 2020 (as measured by the international poverty line of 1.90 US Dollars per day). While there is great uncertainty about the path of the pandemic, the economy is expected to gradually recover from 2021 as aggregate demand rebounds and LNG investments and extractive production gain momentum. Despite the expected recovery, the widespread deployment of COVID-19 vaccines will be at the core of a resilient recovery. This Economic Update explores the implications of COVID-19 for the economy, businesses and households. It makes recommendations for moving forward—in the short-term relief phase, as well as over the medium and longer term in order to 'build back better~^!!^.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; development partners / parceiros de cooperação; economic development / desenvolvimento económico; health - COVID-19 / saúde – COVID-19; health / saúde; private sector / setor privado

Estimating the cost of implementing a facility and community score card for maternal and newborn care service delivery in a rural district in Uganda - Ssebagereka, Anthony; Apolot, Rebecca Racheal; Nyachwo, Evelyne Baelvina; Ekirapa-Kiracho, Elizabeth (International Journal for Equity in Health, 2021)
This paper aimed at estimating the resources required to implement a community Score Card by a typical rural district health team in Uganda, as a mechanism for fostering accountability, utilization and quality of maternal and child healthcare service.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; Health PEA; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; community scorecard (CSC) / cartão de pontuação comunitária (CPC); gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; youth / juventude

Análise da Proposta do Orçamento do Estado 2021 - Mussagy, Ibraimo H. (Observatório do Meio Rural, 2021)
A actual Proposta do Orçamento do Estado (POE) 2021 é a segunda para o quinquénio 2020-2024 e foi elaborada num contexto de transformações económicas e sociais impostas por um novo “normal” provocado pela pandemia da COVID-19, que resultou na maior recessão mundial estimada em cerca de -4.9% para 2020. Essa recessão foi causada pelas medidas de contenção que resultaram na paralisação da actividade económica em grande parte das economias. Em linha com as actuais tendências da economia mundial, a economia Moçambicana também tem registado uma desaceleração (parágrafo 2 da POE 2021). Este texto tem a finalidade de analisar a POE 2021, tendo em conta este contexto. Para tal, a análise foi feita com base nos seguintes documentos: Plano Económico e Social (PES) 2021, POE 2021, mapas integrantes¹, leis orçamentais anteriores e os Relatórios de Execução Orçamental (REO) recentes. Faz-se a articulação destes documentos para se poder perceber a evolução das componentes da POE 2021. O texto compreende três secções, nomeadamente a introdução, a análise do orçamento, onde, de forma específica, o texto analisa os pressupostos macroeconómicos subjacentes à proposta, a evolução das receitas e das despesas, faz uma discussão sobre o défice orçamental, destaca os orçamentos sectoriais com enfase para agricultura, onde o projecto SUSTENTA prevalece em grande parte da discussão, aborda a questão da descentralização e discute o endividamento público, e, na última secção, apresenta-se o resumo das constatações.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; agriculture / agricultura; budget / orçamento; decentralization / descentralização; education / educação; health / saúde

Relatório de Pesquisa Desigualdades e Resistência em Tempos de Pandemia: Impactos Da COVID-19 Nas Mulheres do Mercado Informal - Osório, Conceição; Loforte, Ana Maria; Vilanculo, Sérgio (WLSA Moçambique, 2021)
Este relatório de pesquisa buscou especificamente identificar no contexto mundial, regional e nacional as estratégias e as políticas públicas relativamente à situação das raparigas e mulheres, analisar as narrativas e discursos das organizações da sociedade civil e instituições de pesquisa, tanto as que têm como foco os direitos humanos, como as que definem como objecto a promoção da igualdade de género, e analisar o conteúdo dos media nacionais sobre a Covid-19, com destaque para as representações sobre violência de género. Para a realização da pesquisa foi importante a definição do grupo alvo, as mulheres que trabalham no informal, por serem das mais afectadas pela situação criada pela Covid-19, sendo muito pouco conhecidas as suas vozes, os seus problemas, necessidades e expectativas. A pesquisa foi enquadrada no Projecto “Mulheres e direitos humanos no contexto da COVID-19 em Moçambique” e surgiu no âmbito de uma parceria entre a WLSA Moçambique com as Aliadas e o CESC, procurando conhecer melhor como é que, em situação de pandemia, se configuravam os direitos humanos das mulheres, considerando as desigualdades estruturais e as relações desiguais de poder.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; civil society / sociedade civil; gender / género; health - COVID-19 / saúde – COVID-19; health / saúde; informality / informalidade

Navigating Civic Space in a Time of COVID-19: The Case of Mozambique - Pereira, Crescêncio; Forquilha, Salvador; Shankland, Alex (Institute for Social and Economic Studies, 2021)
This report builds on the Action for Empowerment and Accountability (A4EA) research project Navigating Civic Space, which seeks to analyze the extent to which COVID-19 is contributing to the opening or closing of space for civic action in three countries, namely Mozambique, Nigeria and Pakistan. Focusing on Mozambique, the report uses theoretical and methodological tools produced by the work stream and is essentially structured around the three main research questions: What is known about the civic space trend in Mozambique before the arrival of the COVID-19 pandemic?; How are different actors responding to the COVID-19 pandemic affecting the civic space in Mozambique?; What are the medium and long term implications for governance in Mozambique?
Keywords: G - Mozambique / Moçambique; L - english / inglês; civic space / espaço cívico; health - COVID-19 / saúde – COVID-19

African Economic Outlook 2021: From Debt Resolution to Growth: The Road Ahead for Africa - African Development Bank (African Development Bank, 2021)
The 2021 edition of the African Economic Outlook focuses on debt resolution, governance, and growth in Africa. Chapter 1 examines Africa’s growth performance and outlook amid the COVID–19 pandemic. The chapter emphasizes policy options to mitigate the effects of the pandemic in the short, medium, and long terms. Chapter 2 explores the causes and consequences of Africa’s debt dynamics by showing how the changing structure and composition of debt create vulnerabilities. In chapter 3, the report takes stock of the challenges in the current global architecture for debt resolution and explores the link between governance and growth with an emphasis on proposed reforms to improve the processes of debt resolution, governance, and sustainable growth
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; governance / governação; health - COVID-19 / saúde – COVID-19

A COVID-19 e suas implicações na governação municipal em Moçambique: um estudo de caso a partir do município de Gondola - António, Bernardino (Desafios para Moçambique 2021, 2021)
Tomando como exemplo o município de Gondola, na província de Manica, este artigo analisa as implicações da COVID-19 na governação municipal, destacando a interacção entre a edilidade e os munícipes no desenvolvimento do mesmo. O texto defende o argumento segundo o qual, apesar de a COVID-19 ter impactado negativamente nas lógicas do Governo de Gondola, a pandemia, por si só, não constitui factor explicativo para a fraca interacção entre as autoridades e os munícipes, pois os baixos níveis de interacção entre os Vereadores e os cidadãos constitui um problema de carácter estrutural, que caracteriza o Governo não só ao nível das autarquias, mas também a outros níveis de governação em Moçambique. O artigo está organizado em três secções, além da introdução. Na primeira secção, faz se uma breve caracterização do município de Gondola, mostrando o contexto da análise aqui feita. Na segunda secção, aborda-se o papel dos municípios na gestão da COVID-19 em Moçambique. Na terceira secção, descreve-se a COVID-19 e as suas implicações no Governo de Gondola, destacando a questão da interacção entre as autoridades municipais e os munícipes. O artigo resulta de uma pesquisa realizada no município de Gondola em 20206, no âmbito do projecto de pesquisa «Barómetro da Governação Municipal», em curso no Instituto de Estudos Sociais e Económicos (IESE) desde 2017. A pesquisa baseou-se numa metodologia qualitativa, com recurso a entrevistas semiestruturadas, discussões em grupos focais e observação no terreno, realizadas em 10 bairros do município de Gondola, nomeadamente Mazicuera, Mucessua, Josina Machel, Bengo, Nhachoco, Eduardo Mondlane, 3 de Fevereiro, 7 de Abril, Francisco Manyanga e 25 de Junho. Foram realizadas quatro discussões em grupos focais e nove entrevistas semiestruturadas com moradores, membros do Governo Municipal (Presidente e Vereadores), membros da Assembleia Municipal, líderes comunitários, comerciantes locais e organizações da sociedade civil. A pesquisa de campo decorreu ao longo de 15 dias, entre Novembro e Dezembro de 2020
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; governance / governação; health - COVID-19 / saúde – COVID-19; politics / política

«Se alguém está cansado de viver» A economia informal e a segurança social - Castel-Branco, Ruth (Desafios para Moçambique 2021, 2021)
A fraca resposta do Estado aos impactos socioecónomicos da pandemia da COVID-19 salientou a necessidade de reformular o sistema da Segurança Social em Moçambique; de evoluir de um paradigma social trabalhista para um paradigma que reconhece a centralidade da economia informal e a responsabilidade redistributiva do Estado, assente num contrato social. Não existe uma única abordagem para a inclusão dos trabalhadores informais na protecção social. A economia informal é extremamente diversificada e estratificada por tipo de atividade, formas de organização e estruturas de rendimento. Portanto, é necessário considerar abordagens diferenciadas que respondem às várias realidades dos trabalhadores informais, incluindo a ausência de um empregador e a irregularidade dos rendimentos. As medidas de Segurança Social Não-Contributiva introduzidas durante a pandemia podem servir com base para um sistema redistributivo mais robusto. Mas no reforço do papel redistributivo do Estado, é importante não absolver os empregadores da sua responsabilidade de reprodução social. Por exemplo, o Regulamento de Trabalho Doméstico estipula que, por motivos do Instituto Nacional de Segurança Social, os trabalhadores domésticos devem ser considerados trabalhadores por conta própria (RdM, 2008). Porém, segundo a Lei de Trabalho (RdM, 2007b), os trabalhadores por conta própria são aqueles que: podem escolher os processos e meios de trabalho, sendo estes da sua propriedade, no todo ou em parte; não estão sujeitos a horários de trabalho, salvo se os mesmos resultarem da lei ou regulamentos; não se integram na estrutura produtiva ou cadeia hierárquica de uma única empresa, nem constituem elemento essencial ao desenvolvimento dos objectivos de qualquer entidade empregadora; e podem fazer-se substituir livremente. Esta inconsistência reflecte o poder negocial da classe empregadora na definição do Regulamento. Apesar de não serem trabalhadores informais, os trabalhadores domésticos são informalizados pela falta de protecções laborais e sociais adequadas e a sua devida aplicação. Portanto, é crítico garantir que medidas orientadas à expansão da Segurança Social – seja a Segurança Social Contributiva ou Não-Contributiva – estejam articuladas com medidas para reforçar os direitos laborais num contexto de fraca fiscalização, informalização e informalidade generalizada.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; Social security / segurança social; health - COVID-19 / saúde – COVID-19; informality / informalidade; society / sociedade

Health sector analysis: political economy of decentralised health service provision - MAP Consult; Konung International (POTENCIAR, 2021)
This report offers POTENCIAR and the British High Commission (BHC) an analysis of how power arrangements influence the main social, political, and economic factors in service provision and decentralised governance in Mozambique. The results of the study will be used to refine POTENCIAR’s strategy and approach, as well as the design of PAIs in the health sector. While PAIs address issues across multiple sectors, sector analysis will also consider potential entry points for, as well as barriers to, the improvement of intersectoral coordination and strengthening of citizen participation. Through an analysis of the political economy of the health sector, this report will examine the formal and informal power structures and institutions that influence service provision and the decentralised governance of the health sector. Methodologically, the study is based on a bibliographic and documentary review of governance, decentralisation, and accountability across Mozambique, and the health sector in particular. These data are complemented by interviews with key informants who have knowledge of or actively participate in the health sector. The study is based on the northern province of Nampula, which POTENCIAR has identified for the implementation of its first pro-accountability initiative in the health sector.
Keywords: *non-public; G - Mozambique / Moçambique; GP - Nampula; Health PEA; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; health - health services / serviços de saúde; health / saúde

Política económica em contexto de pandemia: uma reflexão em trono das medidas de mitigação dos efeitos da COVID-19 sobre a economia de Moçambique - Muianga, Carlos; Ibraimo, Yasfir (Desafios para Moçambique 2021, 2021)
Este artigo pretende reflectir sobre as medidas para mitigação dos efeitos da COVID-19 na economia de Moçambique e as suas implicações analíticas. Diferentemente de estudos anteriores sobre os impactos da pandemia e das medidas de mitigação adoptadas pelo Governo de Moçambique (Mapisse et al., 2021), este artigo parte da análise da estrutura da economia e do seu padrão de acumulação nas últimas duas décadas, na tentativa de melhor questionar a eficácia destas medidas. O artigo argumenta que, à semelhança das crises cíclicas pelas quais a economia de Moçambique passou nas últimas décadas (Castel-Branco and Ossemane, 2010; Castel-Branco, 2017), a crise provocada pela COVID-19 expõe e exacerba as fragilidades e vulnerabilidades do padrão de crescimento e a sua limitada capacidade em resolver questões centrais de transformação social e económica. Dadas as fragilidades e vulnerabilidades associadas ao padrão de crescimento económico e ao «modelo» de política económica, as medidas de mitigação dos efeitos da pandemia sobre a economia são limitadas relativamente à complexidade dos impactos socioeconómicos da COVID-19. Mais do que a sua limitada capacidade para relançar a actividade produtiva, dada a estrutura da economia, as mesmas são insuficientes para lidar com os impactos mais severos da pandemia, sobretudo para os grupos sociais mais vulneráveis. Entretanto, a COVID-19 tem chamado a atenção à necessidade de acção política e mudança «radical» na prossecução da política económica, incluindo o papel do Estado na economia (Stevano et al., 2021). Contudo, as principais medidas de política económica até então adoptadas continuam a seguir um «modelo» que, há décadas, se tem mostrado ineficaz em resolver, a médio e longo prazo, as questões de transformação económica e social do País. Este artigo está organizado em quatro secções, incluindo a introdução. A segunda faz uma breve descrição e análise da estrutura da economia e do padrão de crescimento económico em Moçambique, nas últimas duas décadas. O objectivo desta secção é fornecer uma base analítica que ajude a interrogar as medidas de mitigação dos efeitos da COVID-19 sobre a economia, enquanto, ao mesmo tempo, ajuda a explicar o tipo de economia que a pandemia encontrou, as suas características fundamentais e o seu funcionamento. A terceira secção descreve as principais medidas adoptadas pelo BM e pelo Governo para mitigar os efeitos da COVID-19, questionando-as em função da estrutura da economia e do quadro de implementação de política monetária e fiscal e as suas contradições e tensões. A quarta secção conclui e avança algumas questões para reflexão.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico; government policy / politica governamental; health - COVID-19 / saúde – COVID-19

Navengando o espaço cívico em contexto da pandemia da COVID-19: o caso de Moçambique - Pereira, Crescêncio; Forquilha, Salvador; Shankland, Alex (Desafios para Moçambique 2021, 2021)
Este artigo circunscreve-se no âmbito do projecto de pesquisa Navigating Civic Space in a Time of Covid-19 (Navegando o Espaço Cívico em Tempo da Covid-19), que procurou analisar em que medida o coronavírus estava a contribuir para a abertura ou o fechamento do espaço para a acção cívica em três países, nomeadamente Moçambique, Nigéria e Paquistão. Com enfoque em Moçambique, este artigo serve-se de ferramentas teóricometodológicas produzidas pela equipa de pesquisa dos três países acima mencionados e estrutura-se essencialmente em torno das três principais questões da pesquisa: · O que se sabe sobre a tendência do espaço cívico em Moçambique antes da chegada da pandemia da COVID-19? · Como é que diferentes actores estão a responder à pandemia da COVID-19 e de que maneira estas respostas vêm a afectar o espaço cívico em Moçambique? · Quais são as implicações de médio e longo prazo para a governação em Moçambique? O material usado para a elaboração do artigo foi produzido com base numa abordagem metodológica que combina quatro componentes, nomeadamente a) avaliação de base sobre a natureza do espaço cívico em Moçambique antes da pandemia da COVID-19; b) painel virtual de observação, constituído por especialistas moçambicanos da sociedade civil, com reuniões mensais; c) análise de meios de comunicação social com recurso a catálogos de eventos; d) entrevistas com uma selecção de informantes-chave para complementar a informação produzida pelas outras componentes. Neste contexto, foi elaborado um relatório de avaliação de base (Pereira, C. & Forquilha, 2020) e foram realizadas seis sessões de painéis virtuais de observação. Com temas previamente acordados, as sessões mensais tinham a duração de duas horas e os assuntos nelas discutidos eram gravados, registados e transformados em relatórios mensais que, posteriormente, eram discutidos em encontros mensais internacionais, envolvendo equipas de pesquisa do IDS, IESE e os parceiros de pesquisa da Nigéria e do Paquistão.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; civic space / espaço cívico; health - COVID-19 / saúde – COVID-19; politics / política

A COVID-19 e as vacinas em Moçambique: algumas notas para reflexão a partir da teoria <sociedade de risco> - Posse, Lúcio (Desafios para Moçambique 2021, 2021)
No presente texto, procuro, por meio da teoria «Sociedade de Risco», elaborada por Ulrich Beck (2011 [1986]), reflectir sobre como os «moçambicanos» elaboram os seus significados e sentidos de risco em relação à COVID-19 e à vacina, e como estes têm estado a desenvolver os seus comportamentos na resposta à pandemia e à vacina. Em termos pragmáticos, procuro chamar a atenção para a necessidade da compreensão dos riscos, como forma de tentar fazer com que as respostas, não só à COVID-19, mas também a outros fenómenos, não fiquem reféns das percepções dos riscos, ao ponto de as comprometer – no sentido de ignorar ou exagerar –, porque, como refere (Beck, 2002:4), «o maior perigo não é o risco [em si], mas a percepção [que as sociedades podem desenvolver] do risco [ao ponto dos seus comportamentos se tornarem num obstáculo para a resolução dos problemas]». Com este texto, mostro que a percepção – à semelhança de outros contextos – que a sociedade moçambicana tem da COVID-19 e da vacina são produto da «racionalidade social do risco», na medida em que os seus sentidos e significados são determinados por questões socioeconómicas, culturais (particularmente os hábitos alimentares), raciais, climáticas, políticas e por experiências: (i) da colonização no uso da medicina para dominar e fazer experimentos clínicos nos africanos, e (ii) da falta de tratamento e da incapacidade dos sistemas de saúde darem resposta ao vírus e aos efeitos colaterais das vacinas, que por vezes causam a morte. Ademais, estas percepções têm estado a estruturar o comportamento dos moçambicanos, primeiro, no que se refere à doença, ao manifestarem, de um lado, a indiferença e/ou despreocupação por considerarem que a doença é dos «outros» e, do outro, pela tomada de medidas de prevenção, num claro sinal de pânico e; segundo, quanto à vacina ao manifestarem, de um lado, a desconfiança em relação à origem, segurança e objectivos da vacina e, do outro, ao receberem a vacina por acreditarem que, em termos de riscos/ benefícios, há muito mais benefícios em receber a vacina.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; health - COVID-19 / saúde – COVID-19; politics / política

A recessão económica em Moçambique: foi a COVID-19? Um olhar a partir do sector externo - Sambo, Michael Godet (Desafios para Moçambique 2021, 2021)
Este artigo argumenta que a crise económica em Moçambique não resulta da eclosão da pandemia em si, e dos seus efeitos directos na economia moçambicana, mas sim, que a pandemia exacerbou uma crise pré-existente. O artigo resulta de análise bibliográfica e documental, com ênfase para a análise de dados estatísticos de múltiplas fontes internacionais e nacionais, destacando as fontes oficiais, e analisa as dinâmicas económicas no contexto da COVID-19, com enfoque nas relações económicas de Moçambique com o resto do Mundo desde antes da eclosão da pandemia até aos princípios de 2021. Além da introdução, este artigo é desenvolvido em duas secções seguidas da conclusão. A primeira secção analisa as dinâmicas das políticas públicas no contexto da dependência externa, e a segunda investiga as dinâmicas da economia de Moçambique em relação ao resto do mundo, analisando os antecedentes e as variações no âmbito da COVID-19, com vista a aferir a sua relação; segue-se finalmente uma conclusão e implicações da análise.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico; health - COVID-19 / saúde – COVID-19

Lições da COVID-19 sobre o papel da poupança doméstica: O que dizer de Moçambique? - Siúta, Moisés (Desafios para Moçambique 2021, 2021)
O presente artigo procura discutir lições que se podem tirar em relação ao papel da poupança para Moçambique, no âmbito da pandemia da COVID-19. O artigo inspira-se na pesquisa sobre poupança, pobreza e protecção social desenvolvida pelo Instituto de Estudos Sociais e Económicos (IESE), que estabelece a ligação entre poupança e protecção social, tendo em vista estudar mecanismos que permitam desenvolver um sistema de protecção social financeiramente viável em Moçambique (Siúta, 2019b). O objectivo deste artigo é estabelecer a ligação entre a poupança e a COVID-19, discutindo o seu papel no âmbito da resposta à pandemia. A metodologia usada, além da revisão de literatura, inclui a exploração de dados sobre a evolução da pandemia em diversos países, fornecidos pela Organização Mundial da Saúde (OMS/WHO (World Health Organization)), cuja base de dados foi preparada e disponibilizada publicamente por Ritchie et al. (2020). Para completar a análise através da exploração de dados sobre a economia dos países, analisando, principalmente, a evolução da poupança doméstica e do produto dos países, recorreu-se à base de dados dos indicadores de desenvolvimento dos países, disponibilizada pelo Banco Mundial (World Bank, 2021). O artigo, incluindo a presente introdução, subdivide-se em quatro secções. Nas secções a seguir, na primeira, discute-se a relevância da poupança doméstica, no contexto da pandemia da COVID-19, com base numa abordagem teórica da poupança; a segunda secção, baseada em dados sobre a poupança doméstica e a capacidade de testagem e vacinação contra a COVID-19, procura discutir a relevância da poupança doméstica nos países ao redor do Mundo, incluindo o caso de Moçambique. Na última secção, apresenta-se uma breve discussão sobre o contexto moçambicano e a relevância da poupança doméstica.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; health - COVID-19 / saúde – COVID-19; poverty / pobreza; social protection / proteção social; society / sociedade

Acção Social em contexto de COVID-19: Respostas e desafios em Moçambique - Siúta, Moisés; Félix, Matusse (Desafios para Moçambique, 2021, 2021)
O presente artigo tem como objectivo partilhar as medidas de resposta em contexto da COVID-19 implementadas pelo INAS, no âmbito dos programas do Governo para assistência social, tendo em conta que a eclosão da pandemia constituiu mais um factor a colocar o subsistema nacional da Segurança Social Básica (SSB) sob pressão, a fim de dar resposta a um grupo cada vez mais crescente de cidadãos moçambicanos em situação de extrema pobreza e de vulnerabilidade. O artigo está divido em cinco secções, incluindo esta introdução. São abordados os seguintes assuntos: segunda secção, a dimensão da COVID-19 e a relevância da assistência social; terceira, resposta à pandemia no âmbito dos programas do INAS; quarta, os principais desafios da acção social na resposta à pandemia; e a quinta secção apresenta considerações finais e possíveis lições
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; government policy / politica governamental; health - COVID-19 / saúde – COVID-19; social action / ação social; social protection / proteção social

Essencial para quê? Uma visão global de reprodução social sobre a reorganização do trabalho durante a pandemia da COVID-19 - Stevano, Sara; Ali, Rosimina; Jamieson, Merle (Desafios para Moçambique 2021, 2021)
O presente artigo pretende investigar a noção de trabalho essencial através de uma lente feminista global centrada na reprodução social. Abordam-se duas questões principais: primeiro, o que é trabalho essencial e como é que esta terminologia tem sido utilizada em diferentes países do Sul e do Norte Global. Através de uma revisão da literatura, decretos, documentos orientadores e artigos de jornal, procedemos ao mapeamento dos significados de trabalho essencial em todo o Mundo, utilizando como exemplos África do Sul, Brasil, Canadá, Inglaterra, Índia, Itália e Moçambique. Em segundo lugar, tomando como ponto de partida a afirmação feita pelos teóricos da reprodução social de que o reconhecimento de formas de trabalho desvalorizadas como essenciais constitui uma via para revalorizar o trabalho socialmente reprodutivo (Bhattacharya, 2020; Stevano et al., 2021), perguntamos se este potencial foi explorado até agora e, caso contrário, que limitações, omissões e contradições o estão a impedir. A perspectiva global é complementada por um «foco» sobre Moçambique como um país de baixa renda, localizado no Sul Global, ocupando uma posição periférica nas economias globais e regionais e com uma grande percentagem de trabalhadores vulneráveis e essenciais. As ilustrações de Moçambique baseiam-se na investigação preliminar sobre o trabalho nas agro-indústrias, realizado pelas autoras antes da pandemia, em combinação com a revisão de artigos de jornal, documentos orientadores, observações e evidência primária seleccionada durante a pandemia
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; employment / emprego; health - COVID-19 / saúde – COVID-19; social reproduction / reprodução social

Qualidade da assistência pré-natal em Nampula, Moçambique - Muleva, Belarmina Reis (Universidade de São Paulo, 2020)
A realização da consulta pré-natal de alta qualidade está diretamente relacionada aos melhores indicadores maternos e fetais e à prevenção de morbimortalidade materna. Em Moçambique, estudos sobre assistência pré-natal mostram que a maior parte das mulheres fez pré-natal, mas apenas metade fez as quatro ou mais consultas preconizadas pelo Ministério da Saúde. Além disso, as gestantes têm se apresentado aos centros de saúde para fazerem sua primeira consulta pré-natal somente no final do segundo trimestre da gestação. Essas questões mostram que a qualidade da assistência ao pré-natal é ainda um desafio, embora haja poucos estudos sobre o tema naquele contexto. Objetivo: Avaliar a qualidade da assistência pré-natal entre as mulheres do município de Nampula, em Moçambique. Método: Trata-se de um estudo quantitativo, do tipo transversal, realizado no município de Nampula, em Moçambique, na África. A amostra constou de 393 mulheres de 18 a 49 anos, com parto ocorrido em maternidade ou no domicílio no segundo semestre de 2019. As entrevistas foram conduzidas por meio de instrumento estruturado, aplicado face-a-face, até 15 dias após o parto. A qualidade da assistência pré-natal foi analisada com base nas diretrizes do Ministério da Saúde de Moçambique. A qualidade do pré-natal foi categorizada em inadequada e adequada. Modelos de regressão logística múltipla foram conduzidos para analisar os aspectos associados a ter realizado pré-natal adequado. Resultados: As mulheres participantes do estudo tinham, em média, 26 anos de idade, e metade tinha ensino primário (52,4%). Embora todas as mulheres tenham realizado o pré-natal, apenas 13,0% tiveram o pré-natal classificado como adequado. Mulheres que realizaram pré-natal em gestações anteriores (OR=4,28; IC95%=1,45-12,62) e com gravidez planejada (OR=2,51; IC95%=1,11-5,68) foram as que tiveram mais chance de ter um pré-natal adequado. Observou-se que a assistência pré-natal não atendeu ao que é preconizado, como a idade gestacional de início do pré-natal, número mínimo de consultas a serem feitas, realização de alguns exames (hemograma, glicemia, tipagem sanguínea e fator Rh) e oferta de orientações sobre sinais de risco e de parto. Quanto à satisfação com a assistência pré-natal recebida, mais da metade das mulheres mostrou-se insatisfeita com o tempo de espera para ser atendida pela profissional de saúde. Conclusão: De modo geral, os critérios preconizados para que uma assistência ao pré-natal seja de alta qualidade não estão incorporados na prática clínica no município de Nampula.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; L - portuguese / português; gender / género; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - health services / serviços de saúde; health - maternal and child / saúde - materno-infantil; health / saúde

Covid-19: Organizações questionam gastos do Governo moçambicano | DW | 11.08.2020 - Deutsche Welle (DW.COM, 2020)
Em Moçambique, a sociedade civil aponta falta de transparência e pede esclarecimentos ao Governo sobre os 14 mil contratos sem concurso público e os 68 mil milhões de meticais gastos durante o estado de emergência.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; accountability / responsabilização; health - COVID-19 / saúde – COVID-19; health / saúde; transparency / transparência

First confirmed occurrence of the yellow fever virus and dengue virus vector Aedes (Stegomyia) luteocephalus (Newstead, 1907) in Mozambique - Abílio, Ana Paula; Kampango, Ayubo; Armando, Eliseu J.; Gudo, Eduardo S.; das Neves, Luís C. B.; Parreira, Ricardo; Sidat, Mohsin; Fafetine, José M.; de Almeida, António Paulo G. (Parasites & Vectors, 2020)
Mozambique, same as many other tropical countries, is at high risk of arthropod-borne virus (arbovirus) diseases and recently two dengue virus (DENV) outbreaks occurred in the northern part of the country. The occurrence of some important vector species, such as Aedes (Stegomyia) aegypti (Linnaeus) and Ae. (Stg.) albopictus (Skuse), besides several other sylvatic vectors, have been reported in the country, which may indicate that the transmission of some arboviruses of public health importance may involve multiple-vector systems. Therefore, knowing the occurrence and distribution of existing and the new important vectors species, is crucial for devising systematic transmission surveillance and vector control approaches. The aim of this study was to map the occurrence and distribution of mosquito species with potential for transmitting arboviruses of human and veterinary relevance in Niassa Province, Northern Mozambique.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Lago; GP - Niassa; L - english / inglês; health / saúde

Health, development, and institutional factors: The Mozambique case - Garrido, Paulo Ivo (2020)
Abstract: The central aim of this text is to show the impact institutions have on the performance of the health sector in Mozambique. The text shows that of the social determinants of health, institutions play a central role in the performance of the Mozambican health sector—and, through it, economic and social development—particularly for the poorer and more vulnerable, such as children, women, the disabled, and the elderly. It is also argued that the deficiencies and inefficiencies of the operation of the health sector in Mozambique are largely the result of the fact that the institutions with influence on the health sector are controlled by a minority of privileged people who do not give the appropriate priority to the basic health needs of the majority of the population. Finally, it is argued that the most important institutional measures for improving the state of health of Mozambicans are the revision of the Constitution of the Republic, the strengthening of the National Health System (particularly the National Health Service), and the reduction of poverty and economic and social inequality.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; health - social determinants of health / saúde - determinantes sociais da saúde; health / saúde; institutions / instituições

Saúde, desenvolvimento e factores institucionais: o caso de Moçambique - Garrido, Paulo Ivo (2020)
Este texto tem por objectivo central mostrar o impacto que as instituições têm no desempenho do sector da Saúde em Moçambique. No texto demonstra-se que, de entre os Determinantes Sociais da Saúde, as instituições têm um papel central no desempenho do sector da Saúde — e, por seu intermédio, no desenvolvimento económico e social — dos moçambicanos, em especial dos mais pobres e mais vulneráveis, como as crianças, as mulheres, as pessoas com deficiência e os idosos. Argumenta-se também que as deficiências e ineficiências do funcionamento do sector da Saúde em Moçambique resultam em larga medida do facto de as instituições com influência no sector da Saúde serem controladas por uma minoria de privilegiados que não dá a prioridade devida às necessidades básicas em saúde da maioria da população. Finalmente, argumenta-se que as medidas de carácter institucional mais importantes para a melhoria do estado de saúde dos moçambicanos são a revisão da Constituição da República, o reforço do Sistema Nacional de Saúde (em particular do Serviço Nacional de Saúde) e a redução da pobreza e das iniquidades económica e social.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; access to services / acesso a serviços; accountability / responsabilização; health - social determinants of health / saúde - determinantes sociais da saúde; health / saúde; institutions / instituições

Do male engagement and couples’ communication influence maternal health care-seeking? Findings from a household survey in Mozambique - Sitefane, Gilda G.; Banerjee, Joya; Mohan, Diwakar; Lee, Connie S.; Ricca, Jim; Betron, Myra L.; Cuco, Rosa Marlene Manjate (BMC Pregnancy and Childbirth, 2020)
This study explored effects of couples’ communication and male participation in birth preparedness and complication readiness (BPCR) on delivery in a health facility (“institutional delivery”). A cross-sectional, baseline household survey was conducted in November 2016 prior to an integrated maternal and child health project in Nampula and Sofala Provinces in Mozambique.
Keywords: G - Mozambique / Moçambique; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Unpacking the Potential Socioeconomic Impact of the Coronavirus Pandemic in Mozambique: A United Nations Situation Analysis and Policy Recommendations - United Nations Mozambique (United Nations, 2020)
The Coronavirus pandemic arrives in Mozambique at a time when, after several years of modest economic performance, the Mozambican economy was starting to show signs of recovery. Hence, the latest projections of the IMF of November 2019 had the Mozambican economy growing at 6% in 2020, with medium term projections reaching 9% and above after 2023, following the initiation of LNG exploration operations in the north of the country. Despite this improving macroeconomic outlook prior to the outbreak of the Coronavirus pandemic, living conditions for many Mozambicans remain harsh. Poverty afflicts almost half of the population, 46.1% according to the 2014/15 national household survey, and many people continue without access to basic services, with the proportion of Mozambicans with access to basic water supply, basic sanitation and electricity remaining at very low levels: 55.7%, 29.4% and 27.4% in 2017, respectively. Moreover, despite improvements in healthcare conditions, Mozambicans, especially women and children, continue to be severely afflicted by disease and sickness. In general, living conditions tend to be worse in rural than in urban parts of the country. The coronavirus pandemic is almost certainly going to change this short- and medium-term economic outlook and could potentially have a very significant socioeconomic impact in Mozambique. However, while all available evidence points in this direction, at this stage it is difficult to ascertain and quantify the extent of this impact, given the speed at which things are changing around the world and the uncertainly surrounding the epidemiological profile of the Coronavirus, which makes it hard to assess how long the containment and lockdown measures being applied around the world will need to remain in place. While a detailed quantification of the socioeconomic impact of the coronavirus pandemic may not be feasible, it is still useful to identify possible transmission channels through which the pandemic may affect the Mozambican economy and society. It is also useful to identify key issues that are likely shape shortand medium-term socioeconomic prospects in Mozambique as a result of the Coronavirus pandemic outbreak in Mozambique. The following sections outline some of these.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico; health - COVID-19 / saúde – COVID-19; health / saúde

Baseline Assessment of Facility and District Capacity: Alcançar Qualidade de Serviços de Saúde para Mulheres e Crianças - USAID; fhi360; Alcançar (FHI 360, 2020)
The Alcançar Baseline Assessment of Facility and District Capacity was conducted to establish an evidence base against which to measure project performance and impact over the life of the project and to inform project priorities and planning. The assessment includes a census of health centers and hospitals in Nampula province - the population of facilities that the project is expected to influence. Trained data collection teams interviewed facility and district staff to collect current information on (1) facility infrastructure and policies, (2) human resources, (3) ordering and management of maternal and child health (MCH) commodities, (4) provision of MCH services (5) knowledge of MCH care components, and (6) emergency referral capacity. Additionally, they reviewed and extracted data from facility registers over a 6-month period and observed antenatal care (ANC) consultations. Data collectors visited each of the district health offices (Serviço Distrital de Saúde, Género, Criança e Acção Social, SDSMAS) to gather information on district health capacity to provide clinical mentoring, implement quality improvement and death audits, and manage commodities. This assessment report presents selected results.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; access to services / acesso a serviços; health - maternal and child / saúde - materno-infantil; health / saúde

A segurança social em Moçambique: conversa para o boi dormir ou um instrumento de redistribuição viável? - Castel-Branco, Ruth Kélia (Desafios para Moçambique 2020, 2020)
Nas últimas décadas, houve uma ressurgência de interesse na Segurança Social como instrumento redistributivo capaz de reduzir a pobreza e a desigualdade e promover o crescimento económico inclusivo. Este crescente interesse a nível global deve-se ao reconhecimento de que o desenvolvimento social não resulta inevitavelmente do crescimento económico, e, aliás, pode ser bem o contrário: que formas de Segurança Social vinculadas ao emprego formal são inadequadas dada a informalidade generalizada e que transferências monetárias não contributivas são possíveis mesmo em países em vias desenvolvimento como Moçambique (Mkandawire, 2011). Nas duas décadas anteriores à crise da Ematum, Moçambique registou um índice de crescimento médio de 7,5 % do PIB. Porém, impulsionado por uma indústria extractiva intensiva em capital, este não resultou em melhores condições de vida para a maioria dos moçambicanos. A Crise da Ematum piorou a situação. Segundo simulações da UNU-WIDER, a crise resultou no aumento do índice da pobreza de 46,1 % em 2014, e de aproximadamente 60 % em 2016 (Mambo et al., 2018). Alarmado pela situação, o antigo Ministro de Administração Estatal, Óscar Monteiro, sugeriu, durante a reunião do Comité Central da Frelimo em Maio de 2019, a rápida expansão do sistema de Segurança Social em Moçambique, mas o Governo optou por não a fazer: "A gravidade da situação requer medidas urgentes. E eu digo isto não porque não é apenas uma questão eleitoral, mas é uma questão de humanidade... Porque é que nós não começamos a distribuir dinheiro, usando a rede existente, ampliando, melhorando... Esse dinheiro não se vai perder... Esse dinheiro vai aumentar o consumo, vai encorajar a produção, vai financiar a recuperação. (Monteiro, 2019)" A crise da Covid expôs mais uma vez a fragilidade do nosso modelo de desenvolvimento económico, e a fraqueza dos mecanismos de redistribuição existentes. Projecções da UNU-WIDER concluíram que apenas 7 % dos moçambicanos tinham as condições para sobreviver a um lockdown total (Jones, Egger & Santos, 2020). O Governo acabou por optar por um lockdown parcial, permitindo que várias instituições públicas e privadas continuassem abertas. No entanto, a questão da expansão da Segurança Social continua oportuna não só como medida de resposta de emergência durante a crise da Covid, mas também como instrumento redistributivo com a capacidade de promover o desenvolvimento inclusivo. Este artigo começa por uma análise do actual sistema de Segurança Social, seguida por uma discussão das medidas de emergência que foram propostas, as sugestões rumo a um sistema de Segurança Social universal, e os riscos – principalmente o risco da financeirização da Segurança Social com a terceirização dos sistemas de registo e pagamentos. O artigo é concluído com uma discussão do tipo de mobilização que será necessário para garantir a expansão adequada da Segurança Social. Como disse o abolicionista Frederick Douglass, «sem luta não há progresso... O poder não concede nada sem demanda. Nunca concedeu e nunca concederá» (Frederick, 1851).
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; Social security / segurança social; health - COVID-19 / saúde – COVID-19; social protection / proteção social

Pânico e Medo: Desafios Dos Media Moçambicanos na Cobertura da COVID-19 - Joanguete, Celestino (Desafios para Moçambique 2020, 2020)
O principal foco do estudo são os diferentes enquadramentos da tonalidade discursiva adoptada pelos media nas suas narrativas sobre o novo coronavírus. Nesta perspectiva, a principal concentração como objecto de estudo são a rádio, a televisão, o jornal e as redes sociais da Internet. Neste último medium, escolhemos analisar especificamente as narrativas do Facebook e WhatsApp por serem as redes sociais mais populares em Moçambique. Socorremo-nos de duas metodologias de estudo bastante presentes no campo das ciências sociais, a análise de conteúdo desenvolvida por Bardin (2006) e a de observação sistemática. Foi fundamental adoptar estes métodos pela vantagem de permitirem recolher dados no momento da ocorrência dos factos, sem criar situações artificiais, e avaliar alguns aspectos para os quais não há outras técnicas de recolha de evidências. Uma análise sobre os diversos atributos descritivos do coronavírus permitiu compreender a construção do discurso mediático e a sua influência social. A análise de conteúdo das narrativas dos media moçambicanos facilitou a compreensão dos elementos constitutivos de textos jornalísticos, nas produções discursivas dos quais os termos, os adjectivos, as imagens, as descrições, o foco e as temáticas desempenham o papel fundamental.
Keywords: *indexed; G - Mozambique / Moçambique; L - portuguese / português; health - COVID-19 / saúde – COVID-19; health / saúde

How do decision-makers use evidence in community health policy and financing decisions? A qualitative study and conceptual framework in four African countries - Kumar, Meghan Bruce; Taegtmeyer, Miriam; Madan, Jason; Ndima, Sozinho; Chikaphupha, Kingsley; Kea, Aschenaki; Barasa, Edwine (Health Policy and Planning, 2020)
Various investments could help countries deliver on the universal health coverage (UHC) goals set by the global community; community health is a pillar of many national strategies towards UHC. Yet despite resource mobilization towards this end, little is known about the potential costs and value of these investments, as well as how evidence on the same would be used in related decisions. This qualitative study was conducted to understand the use of evidence in policy and financing decisions for large-scale community health programmes in low- and middle-income countries. Through key informant interviews with 43 respondents in countries with community health embedded in national UHC strategies (Ethiopia, Kenya, Malawi, Mozambique) and at global institutions, we investigated evidence use in community health financing and policy decision-making, as well as evidentiary needs related to community health data for decision-making. We found that evidence use is limited at all levels, in part due to a perceived lack of high-quality, relevant evidence. This perception stems from two main areas: first, desire for local evidence that reflects the context, and second, much existing economic evidence does not deal with what decision-makers value when it comes to community health systems—i.e. coverage and (to a lesser extent) quality. Beyond the evidence gap, there is limited capacity to assess and use the evidence. Elected officials also face political challenges to disinvestment as well as structural obstacles to evidence use, including the outsized influence of donor priorities. Evaluation data must to speak to decision-maker interests and constraints more directly, alongside financiers of community health providing explicit guidance and support on the role of evidence use in decision-making, empowering national decision-makers. Improved data quality, increased relevance of evidence and capacity for evidence use can drive improved efficiency of financing and evidence-based policymaking.
Keywords: G - Mozambique / Moçambique; L - english / inglês; government policy / politica governamental; health - dignified care / saúde - atendimento humanizado / mau atendimento; health / saúde

Análise do Plano Económico e Social e Orçamento do Estado de 2020 nas Áreas da Saúde, Água e Saneamento - Marrengula, Constantino (Forum de Monitoria do Orçamento, FMO Mais, PAANE, 2020)
Os objectivos e os pilares do PES e OE de 2020 não mudaram, substancialmente, em comparação com o que foram as prioridades do quinquênio 2015-2019. Em linha com os compromissos internacionais, o Governo procurou manter os pesos relativos da despesa nos sectores prioritários, com particular realce para a educação e a saúde. Contudo, o aumento dos preços e dos encargos da dívida, que se seguiu à descoberta das dívidas não declaradas, baixou o valor real das provisões feitas nestes sectores. O valor de cerca de 26 mil milhões de Meticais reservado para a saúde em 2020 representa uma redução em relação ao que tinha sido programado para 2019, não obstante os desafios impostos pela pandemia da Covid19. A redução em termos reais do orçamento da saúde, ocorre num quadro geral, em que todas as metas previstas para o quinquênio passado foram revistas em baixa, ou não foram cumpridas. Por exemplo, num ano eleitoral como foi 2019, a taxa de realização da meta de recrutamento de profissionais para o sistema nacional da saúde situou-se em volta de 50%. As metas do PES e OE 2020 da saúde não parecem suficientes para que o sector recupere dos incumprimentos do quinquênio passado, num contexto que conta com a pandemia da Covid-19. Para o sector de água e saneamento, os acordos assinados com o Exim Bank da Índia, o Banco Mundial, e a SADC deram um novo impulso ao Programa PRAVIDA, mas o nível de realização das metas do PES e do orçamento do sector não foi substancialmente diferente do que aconteceu na saúde. Quando o orçamento aumentou em 2019 a taxa de execução do orçamento baixou para 32%, com incumprimentos em intervenções com impacto directo na pobreza, tanto rural como na zona peri-urbana. A revisão em baixa das metas do PES de 2020, em comparação com o definido para 2019, alarga o tempo necessário para que a intervenção do Estado no sector faça a diferença no acesso à água e saneamento. Num cenário de crescimento populacional, quanto mais conservadora e lenta for a intervenção maior é o atraso na correcção dos problemas identificados, o que certamente tem implicações na materialização dos objetivos de desenvolvimento sustentável. Reverter o cenário que sustenta as taxas de execução sub-óptimas dos orçamentos aprovados e a queda em termos reais das disponibilidades nos sectores prioritários constitui o principal desafio das Finanças Públicas em Moçambique. Embora não esteja claro o que poderá ser o futuro destes sectores depois da pandemia da Covid-19, a curto prazo torna-se importante encontrar formas de usar melhor o que se tem, retomar a trajectoria de sustentabilidade da dívida pública e normalizar as relações com os principais parceiros de apoio orçamental. Como se pode perceber da dinâmica dos indicadores da saúde, água e saneamento, os custos sociais de sub-utilizar o potencial existente e manter o status quo nas Finanças Públicas são demasiado altos para serem desconsiderados.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; economic development / desenvolvimento económico; health - COVID-19 / saúde – COVID-19; health - WASH / saúde - água, higiene e saneamento; health / saúde

Uma Logística Farmacêutica ainda distante de responder às preocupações de saúde do país: as fragilidades orçamentais - N'weti (N'weti, 2020)
A área de logística farmacêutica (LF) é vital pelo facto de assegurar que os medicamentos e produtos médicos estejam disponíveis no país e nos pontos de entrega e inclui seleção de medicamentos, quanti cação, procurement, controle de qualidade, armazenamento, transporte e distribuição. O Governo de Moçambique reconhece a importância deste sector e como parte da agenda de reforma do MISAU desenhou o Plano Estratégico de Logística Farmacêutica (PELF) juntamente com o respectivo Plano Operacional (2013). O PELF visa responder a necessidade de providenciar reformas a área de logística farmacêutica melhorando a gestão nanceira, procurement, inventariação, gestão do armazenamento, transporte, distribuição, uso de medicamentos e gestão de recursos humanos. Relatórios disponíveis apontam para a existência de vários desafios na implementação do PELF sendo que a falta de recursos financeiros é um dos maiores desafios para a implementação do quadro de recomendações deste documento. Em Moçambique a LF é actualmente uma das áreas menos favorecidas em termos de dotação orçamental cabendo-lhe 7% do total de envelope de recursos do sector da saúde projectados até 2019 (MISAU/DNPC, 2013). Esta tendência ao ser estacionária ao longo dos próximos 5 anos certamente estará em descompasso com a expansão e aumento da demanda pelos serviços públicos de saúde o que poderá comprometer a prestação do sector de saúde. A actual fonte de nanciamento e práticas de alocação orçamental na área de LF é também problemática. A estimativa da taxa de desperdício de medicamentos e consumíveis representa cerca de 13% do investimento total de $3,929 milhões de dólares da área de Logística Farmacêutica. Uma redução da taxa de desperdício para 5% implicaria numa economia de 332 milhões de dólares durante o PESS 2014 - 2019 (Dutta et al., 2014). Adicionalmente mais de 81% dos fundos para área de medicamentos são nanciados por parceiros externos (Dutta et al., 2014). Esta dependência de fundos externos é preocupante num cenário de incerteza do nanciamento externo ao sector de saúde (Dutta et al., 2014). Os níveis de satisfação da disponibilidade de medicamentos essenciais a nível central apesar de registarem progressos contrastam com a disponibilidade de medicamentos a nível das unidades sanitárias (MISAU, 2013, 2014). Várias Organizações da Sociedade Civil (OSC) incluindo a N ́weti, MSF o CIP tem denunciado sistemáticas rupturas de medicamentos nas unidades sanitárias das províncias do sul, centro e norte do país. Face as rupturas sistemáticas de medicamentos nas unidades sanitárias e a imprevisibilidade do nanciamento externo é crucial que o Governo de Moçambique incremente o volume de nanciamento para a área de LF sobretudo na base de recursos domésticos. A falta de recursos está a afectar grandemente a implementação do PELF e de igual modo a capacidade do sector de saúde em providenciar de forma e ciente serviços de saúde de qualidade.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; budget / orçamento; health / saúde

‘We all have the same right to have health services’: a case study of Namati’s legal empowerment program in Mozambique - Schaaf, Marta; Falcao, Joana; Feinglass, Ellie; Kitchell, Erin; Gomes, Nadja; Freedman, Lynn (BMC Public Health, 2020)
Background: Legal empowerment and social accountability are two strategies that are increasingly used to address gaps in healthcare in low- and middle-income countries, including failure to provide services that should be available and poor clinical and interpersonal quality of care. This paper is an explanatory case study of a legal empowerment effort that employs community paralegals and trains Village Health Committees (VHCs) in Mozambique. The research objective was to explore how community paralegals solved cases, the impact paralegals had on health services, and how their work affected the relationship between the community and the health sector at the local level. Methods: The case study had two components: (1) a retrospective review of 24 cases of patient/community grievances about the health system, and (2) qualitative investigation of the program and program context. The case reviews were accomplished by conducting structured in-depth interviews (IDIs) with those directly involved in the case. The qualitative investigation entailed semi-structured Key Informant Interviews (KIIs) with district, provincial, and national health managers and Namati staff. In addition, focus group discussions (FGDs) were held with Health Advocates and VHC members. Results: Case resolution conferred a sense of empowerment to clients, brought immediate, concrete improvements in health service quality at the health facilities concerned, and seemingly instigated a virtuous circle of rightsclaiming. The program also engendered incipient improvements in relations between clients and the health system. We identified three key mechanisms underlying case resolution, including: bolstered administrative capacity within the health sector, reduced transaction and political costs for health providers, and provider fear of administrative sanction. Conclusions: This study contributes to the limited literature regarding the mechanisms of legal empowerment case resolution in health systems and the impact of hybrid legal empowerment and social accountability approaches. Future research might assess the sustainability of case resolution; how governance at central, provincial, and district level is affected by similar programs; and to what extent the mix of different cases addressed by legal empowerment influences the success of the program.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; empowerment / empoderamento; health / saúde

Redressing the gender imbalance: a qualitative analysis of recruitment and retention in Mozambique’s community health workforce - Steege, Rosalind; Taegtmeyer, Miriam; Ndima, Sozinho; Give, Celso; Sidat, Mohsin; Ferrão, Clara; Theobald, Sally (Human Resources for Health, 2020)
Findings: In-depth interviews (n = 30), key informant interviews (n = 1) and focus group discussions (n = 3) captured experiences and perceptions of employment processes. Intra-household decision-making structures mean women may experience additional barriers to join the APE programme, often requiring their husband’s consent. Training programmes outside of the community were viewed positively as an opportunity to build a cohort. However, women reported difficulty leaving family responsibilities behind, and men reported challenges in providing for their families during training as other income-generating opportunities were not available to them. These dynamics were particularly acute in the case of single mothers, serving both a provider and primary carer role. Differences in attrition by gender were reported: women are likely to leave the programme when they marry, whereas men tend to leave when offered another job with a higher salary. Age and geographic location were also important intersecting factors: younger male and female APEs seek employment opportunities in neighbouring South Africa, whereas older APEs are more content to remain. Conclusion: Gender norms, roles and power dynamics intersect with other axes of inequity such as marital status, age and geographic location to impact recruitment and retention of APEs in Maputo Province, Mozambique. Responsive policies to support gender equity within APE recruitment processes are required to support and retain a gender-equitable APE cadre.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - south / sul; GP - Maputo; Health PEA; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; power / poder

Democracy Index 2020 In sickness and in health? - The Economist Intelligence Unit (The Economist, 2020)
The main focus of the report is the impact of the coronavirus (Covid-19) pandemic on democracy and freedom around the world. It looks at how the pandemic resulted in the withdrawal of civil liberties on a massive scale and fuelled an existing trend of intolerance and censorship of dissenting opinion (see page 14). The report also examines the state of US democracy after a tumultuous year dominated by the coronavirus pandemic, the Black Lives Matter movement and a hotly contested presidential election (see page 42). The results by region are analysed in greater detail in the section entitled “Democracy around the regions in 2020” (see page 26).
Keywords: *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; civil society / sociedade civil; health - COVID-19 / saúde – COVID-19

Mozambique Annual Report 2020: Responding to a Year of Crisis - Wojnar, Andrea M; Lomelin, Jessica; Baker, Daniel; Salu, Karlina; Macangira, Assane; Manjate, Epidauro (UNFPA, 2020)
In the case of Mozambique, the pandemic came on the heels of two destructive cyclones that had devastated large parts of the country in 2019 and whose consequences were still being felt. In northern Mozambique, increasing violence in Cabo Delgado province resulted in a surge of internally displaced persons into local communities in Cabo Delgado, Nampula and Niassa provinces. With host communities ill equipped to meet the needs of those displaced, this population movement created a new humanitarian crisis in the midst of the pandemic. Like all of our governmental, civil society and donor partners, the resilience of UNFPA was tested, and we had to adjust quickly after the first case of COVID-19 was confirmed in March and the Government declared a state of emergency. At the most basic level, women continued to get pregnant and babies were still being born, even in the middle of a pandemic. Addressing the needs of adolescent girls and young women could not be put on hold. Helping to meet the needs of the symbolic target of UNFPA’s work – “the 10-year-old girl” – could not wait until she was 11. Helping to meet her aspirations for the future, advocating and working for her growth and self-fulfillment as a woman leading a healthy, productive and violence-free life – these could not wait a year.
Keywords: G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; health - COVID-19 / saúde – COVID-19; health / saúde; youth / juventude

Prevalence of institutional delivery and its correlates amongst women of reproductive age in Mozambique: a cross-sectional analysis - Yaya, Sanni; Idriss-Wheeler, Dina; Shibre, Gebretsadik; Amouzou, Agbessi; Bishwajit, Ghose (Reproductive Health, 2020)
The healthcare system in Mozambique is striving to reduce the high maternal and child mortality rates and stay on par with the Sustainable Development Goals (SDG 3.1). A key strategy to curb maternal and child mortality is to promote the use of professional childbirth services proven to be highly effective in averting maternal deaths. Currently, little is known about the use of childbirth services in Mozambique. The present study investigated the prevalence of professional healthcare delivery services and identified their sociodemographic correlates.
Keywords: G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde